Influence of anxiety and vital signs before dental treatment - Pilco-Chicaiza, Joselyn G.; Tubon, Irvin; Salinas-Goodier, Carmen; Dalgo-Flores, Violeta; Vaca-Altamirano, Gabriela L. (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: In the dental field, the anxiety that patients experience before attending a dental appointment is a factor that has increased the rates of oral diseases. This could be because patients visit the dentist less frequently and, in many cases, when they already require specialized treatment. Purpose: The purpose of this research was to determine the levels of anxiety and how they influence the vital signs of patients. Methods: The population consisted of 217 patients who received dental care at a health center and accepted the informed consent provided. The Modified Corah Dental Anxiety Scale (MDAS) was used to determine the level of anxiety. Statistical tests, such as the chi-square test, logistic regression, and odds ratio, were used to determine whether anxiety influences vital signs and dental treatment success. Results: All patients showed anxiety, which was distributed as mild (24.9%), moderate (26.7%), high (7.4%), and severe or phobic (41%). Regarding vital signs, 61.8% of patients presented some alteration in blood pressure, 56.7% had alterations in heart rate, 12.4% showed low oxygen saturation levels, and 24% presented alterations in respiratory rate. Despite these factors, 98.6% of the treatments the patients underwent were successful, and only 1.4% were affected by the influence of anxiety. Conclusion: It was found that the patients presented anxiety at different levels, which affected the typical values of vital signs. However, this situation did not affect the success of the dental treatment.